Intelligent Avatar on E-Learning using Facial Expression and Haptic - Ahmad Hoirul Basori; Andi Tenriawaru; Andi Besse Firdausiah Mansur (Universitas Ahmad Dahlan, 2011)
The process of introducing emotion can be improved through three-dimensional (3D) tutoring system. The problem that still not solved is how to provide realistic tutor (avatar) in virtual environment. This paper propose an approach to teach children on understanding emotion sensation through facial expression and sense of touch (haptic).The algorithm is created by calculating constant factor (f) based on maximum value of RGB and magnitude force then magnitude force range will be associated into particular colour. The Integration process will be started from rendering the facial expression then followed by adjusting the vibration power to emotion value. The result that achieved on experiment, it show around 71% students agree with the classification of magnitude force into emotion representation. Respondents commented that high magnitude force create similar sensation when respondents feel anger, while low magnitude force is more relaxing to respondents. Respondents also said that haptic and facial expression is very interactive and realistic.